High frequency repetitive transcranial magnetic stimulation for auditory verbal hallucinations in schizophrenia-spectrum disorders: a naturalistic study - Moulier, Virginie; Lemonnier, Charlotte; Dollfus, Sonia; Guillin, Olivier; Rothärmel, Maud (Frontiers in Psychiatry, 2025)
BackgroundThis study investigates the efficacy of high frequency repetitive transcranial magnetic stimulation (rTMS) for auditory verbal hallucinations in patients with schizophrenia spectrum disorders in routine clinical practice.MethodsIn this monocentric study, data were collected on patients with schizophrenia treated by rTMS for resistant auditory verbal hallucinations from May 2020 to May 2024. Treatment efficacy was regularly assessed.ResultsThe data of 65 patients were collected. There was a significant improvement in the Auditory Hallucination Rating Scale (AHRS, p<0.001), in the Brief psychiatric Rating scale (BPRS, p<0.001) and in the Clinical Global Impression-Improvement (p<0.001) scores over time (from baseline up to six months). The maximum response rate (40%) was obtained after nine weeks of rTMS (on average (SD), after 30.6 (7.8) rTMS sessions). The responders were significantly younger than non-responders (p=0.002). The good tolerance of the rTMS treatment allowed excellent compliance: only seven patients (10.8%) asked to stop rTMS or were non-compliant.ConclusionThese data show the clinical interest and the good tolerance of rTMS in daily practice in patients with schizophrenia suffering from auditory verbal hallucinations.